ANALISIS PERBEDAAN JUMLAH PENYALURAN KREDIT PROPERTI DAN KESEHATAN BANK SEBELUM DAN SESUDAH KEBIJAKAN LOAN TO VALUE - Laksmi Ken Fitri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The aim of this research is to analyze the differences between the amount of credit property and bank health before and after the loan to value policies issued by Bank Indonesia. The health of bank is measured using variable Non Performing Loans. This research analyzed three ltv’s policies in 2012, 2013, and 2015 using wilcoxon signed rank test method. The data of this research came from the three months reports of big five banks who has credit property which is published in their own website. The result of this research showed that there is a significant difference between the amount of credit property and no significant differences towards NPL.. Keywords:, Bank Indonesia policy, Loan to Value, Distribution of Credit Property, Bank’s health, Non Performing Loan (NPL), Wilcoxon Signed Rank Test